Rotator Cuff Footprint Medialization: Indications and Technique - Jordan T. Willis, M.D.; Larry D. Field, M.D. (Arthroscopy Techniques)
When attempting to repair a large, retracted rotator cuff tear, the orthopaedic surgeon can use several techniques such as capsular release and interval slides that can aid in achieving a low-tension repair and thus allow the best environment for healing. One less commonly used strategy is medialization of the greater and lesser tuberosity anatomic rotator cuff footprint. Previous studies have shown that increased tension across the bone-tendon interface decreases healing rates. Medialization effectively decreases the repair tension by reducing the distance from the tendon to its insertion point. As a result, we commonly apply some degree of footprint medialization even for repair of some small- or medium-sized tears if intraoperative assessment shows that reapproximation of the rotator cuff tissue to the anatomic footprint may lead to excessive tension. The purpose of this article is to share our indications and to describe our technique for medialization of the rotator cuff footprint insertion.